2013
DOI: 10.1111/ibi.12126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermittent incubation and clutch covering on the probability of bacterial trans‐shell infection

Abstract: Microbial infection is considered a critical cause of hatching failure in birds. Although several behavioural mechanisms are believed to improve reproductive success in birds, their direct effect on the risk of bacterial trans‐shell infection (BTSI) remains to be tested. Here, we focus on the protective roles of intermittent incubation and covering of the clutch with nest lining during the laying period, when eggs are highly susceptible to BTSI. To our knowledge, this study is the first to use culture‐independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 95 publications
(137 reference statements)
2
39
1
Order By: Relevance
“…Recent results from a study using experimental mallard nests suggested that bacterial infection of waterfowl eggs may have no effect on hatchability (37). In contrast, our results provided evidence that bacterial infection is a mechanism of embryo mortality and may have been responsible for the elevated rates of nonviable eggs reported here.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Recent results from a study using experimental mallard nests suggested that bacterial infection of waterfowl eggs may have no effect on hatchability (37). In contrast, our results provided evidence that bacterial infection is a mechanism of embryo mortality and may have been responsible for the elevated rates of nonviable eggs reported here.…”
Section: Discussioncontrasting
confidence: 53%
“…Our identification of a Neisseria species as the predominant bacterium present in addled eggs appears to be novel, although species in the Neisseria genus have been associated with waterfowl on several occasions. Neisseria animalis was isolated from mallard (Anas platyrhynchos) eggs in the Czech Republic (37). Three isolates that most closely matched N. mucosa, N. canis, and N. meningitidis were isolated from duck feces in New Zealand (38), and N. animaloris was detected in the liver of a shelduck (Tadorna sp.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have found bacterial density on the eggshell to be the main precursor of hatching failure across avian species (Lee et al, 2017;Peralta-Sanchez et al, 2018;Tomas et al, 2018). These findings are not surprising given that previous studies documented that microbes are able to pass through the eggshell into the egg interior and negatively affect embryo viability (Bruce and Drysdale, 1994;Pinowski et al, 1994;Cook et al, 2003;Fonseca et al, 2011;Hansen et al, 2015) or hatchling phenotype (Javurkova et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Hatchability across a range of avian taxa tends to increase with latitude (Koenig 1982), suggesting that factors promoting egg viability may be less strongly selected in temperate regions. Although exposure of eggs to ambient conditions without incubation in the temperate zone quickly reduced viability in some species (Veiga 1992, Godard et al 2007, Javŭrková et al 2014, viability decline was delayed in others (Arnold et al 1987, Arnold 1993, Walls et al 2011. Hatching success was not related to eggshell bacterial load during incubation (Ruizde-Castañeda et al 2011a, b, Walls et al 2012 or affected by cleaning with alcohol (Walls et al 2011).…”
Section: Introductionmentioning
confidence: 99%